The status, policies and outlook for green supply chains in North América - Jaar, Jerry; Sánchez Flores, Rebeca; Courtemanche, Pierre (My University, 2023)
One must credit the global COVID-19 pandemic with elevating supply chains and logistics to a position of prominence in international business. The wake-up call began with shortages of personal protective equipment (PPE), particularly N95 face masks and ventilators. Interruptions in the supply of basic materials due to factory and port shutdowns in China, congested port operations in Valencia, Singapore and Bremerhaven, shortages of workers such as truckers, and warehouse space limitations continue to hamper global trade. Supply chain disruptions have caused widespread and deep negative impacts on production, distribution, and pricing, which has affected both producers and consumers alike. Besides the operational issues surrounding supply chains, there is the challenge of supply chain sustainability. Recognizably, the sustainability of supply chain management means integrating environmentally and financially viable practices into the complete supply chain lifecycle.[1] Presently, sustainability is usually understood as “green” supply chain management; and supply chains, recognizably, have a far greater impact on the environment than any other part of their operations. Operations management scholar S.K. Srivastava defines the scope of Global Supply Chain Managed Solutions (GSCMs) as ranging "from reactive monitoring of general environmental management programs to more proactive practices implemented through various Rs (Reduce, Re-use, Rework, Refurbish, Reclaim, Recycle, Remanufacture, Reverse logistics, etc.).”[2] Green supply chain practices aim to help industries reduce their carbon emissions and minimize waste while maximizing profit. Utilizing paper instead of plastic (a petroleum-based product) is a prime example. Not only is rethinking input materials one way of utilizing and implementing green supply chains practices, but so are reusing waste or by-products, curtailing packaging, redesigning processes, and optimizing transport.[3] Additionally, there are links between improved environmental performance and financial gains. General Motors (GM), for example, reduced disposal costs by USD $12 million by establishing a reusable container program with its suppliers. Perhaps, General Motors may have been less interested in green issues if they were making record profits, but in an attempt to reduce costs in their supply chain, GM found that the cost reductions they identified complemented the company’s commitment to the environment.[4] Factors affecting GSCM practices encompass leadership commitment, technology, brand image and company culture, cost and knowledge.[5] In North America, home to the United States-Mexico-Canada Agreement (USMCA), the continuing drift away from globalization and towards regionalization combined with the growing attention to sustainability by governments, companies, and environmental interest groups, have combined to shine the spotlight on supply chains. The status, policies and outlook for green supply chains in North America are the focus of this monograph—one which we hope will shed light on the progress to date and remaining challenges facing the public and sectors in the US, Mexico, and Canada.
Wilson center
Keywords: Supply chain disruptions; supply chain management; Campus Mexicali